Digital mapping of coastal boulders – high‐resolution data acquisition to infer past and recent transport dynamics. Issue 3 (18th March 2019) - Boesl, Fabian; Engel, Max; Eco, Rodrigo C.; Galang, JaN B.; Gonzalo, Lia A.; Llanes, Francesca; Quix, Eva; Brückner, Helmut
Abstract: Coastal boulder fields provide clues to long‐term frequency‐magnitude patterns of coastal flooding events and have the potential to play an important role in coastal hazard assessment. Mapping boulders in the field is time and labour‐intensive, and work on intertidal reef platforms, as in the present study, is physically challenging. By addressing coastal scientists who are not specialists in remote sensing, this contribution reports on the possibilities and limitations of digital applications in boulder mapping in Eastern Samar, Philippines, where recent supertyphoons Haiyan and Hagupit induced high waves, coastal flooding and boulder transport. It is demonstrated how satellite imagery of sub‐metre resolution (from Pléiades and WorldView‐3 imagery) enables efficient analysis of transport vectors and distances of larger boulders, reflecting variation in latitudes of both typhoon tracks and approaching angles of typhoon‐generated waves. During the investigated events, boulders with a‐axes of up to 8 m were clearly identified to have been shifted for up to 32 m, mostly along the seaward margin of the boulder field. It is, however, hard to keep track of smaller boulders, and the length of a‐axes and b‐axes including their orientation is often impossible to map with sufficient accuracy. Orthophotographs and digital surface models created through the application of an unmanned aerial vehicle and the 'Structure from Motion' technique provide ultra‐high‐resolution data, and have the potential to not only improve the results of satellite image analysis, but also those from field mapping and may significantly reduce overall time in the field. Orthophotographs permit unequivocal mapping of a‐axes and b‐axes including their orientation, while precise values for c‐axes can be derived from the respective digital surface models. Volume of boulders is best inferred from boulder‐specific Structure from Motion‐based three‐dimensional models. Battery power, flight speed and altitude determine the limits of the area covered, while patches shielded by the boulders are difficult to resolve. For some tasks, field mapping remains mandatory and cannot be replaced by currently available remote sensing tools: for example, sampling for rock type, density and age dating, recording of lithological separation of boulders from the underlying geological unit and of geomorphic features on a millimetre to decimetre‐scale, or documentation of fine‐grained sediment transport in between the boulders in supratidal settings. In terms of future events, the digital products presented here will provide a valuable reference to track boulder transport on a centimetre to decimetre‐scale and to better understand the hydrodynamics of extreme‐wave events on a fringing reef coastline.